Acinetobacter baumannii and Its relationship to carbapenem resistance : a meta-analysis - Rodrigues, Diego Lucas Neres; Costa, Francielly Morais Rodrigues da; Marques Da Silva, Wanderson; Aburjaile, Flavia; Azevedo, Vasco (MDPI, 2022)
Infections by antibiotic-resistant bacteria are a significant and complex global health issue. In this context, Acinetobacter baumannii is particularly important because of its ability to withstand treatments by β-lactams, such as carbapenem. The objective of this work was to investigate, through systematic analysis and meta-analysis, the chance of resistance to carbapenem in A. baumannii strains. For this, a search was conducted for the PubMed and Cochrane databases based on the keywords: “Acinetobacter baumannii” AND “beta-lactam” OR “penicillin” OR “cephalosporin” OR “cephamycin” OR “carbapenem” OR “monobactam”. The initial search resulted in a total of 90,475 articles. It was filtered based on eligibility criteria, and eight articles were selected for analysis. An odds ratio value equivalent to 3.55 was obtained, indicating a high chance of resistance to the carbapenem of strains of the species. Therefore, it is supposed that A. baumannii infection cases have a high probability of not responding adequately to treatments based on carbapenem.